2006
DOI: 10.1101/gad.406406
|View full text |Cite
|
Sign up to set email alerts
|

Mitf regulation of Dia1 controls melanoma proliferation and invasiveness

Abstract: It is widely held that cells with metastatic properties such as invasiveness and expression of matrix metalloproteinases arise through the stepwise accumulation of genetic lesions arising from genetic instability and "clonal evolution." By contrast, we show here that in melanomas invasiveness can be regulated epigenetically by the microphthalmia-associated transcription factor, Mitf, via regulation of the DIAPH1 gene encoding the diaphanous-related formin Dia1 that promotes actin polymerization and coordinates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

70
652
3
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 533 publications
(733 citation statements)
references
References 59 publications
70
652
3
8
Order By: Relevance
“…In addition to its role in differentiation, MITF represses cell proliferation by activating the expression of cell-cycle inhibitors, such as p16 INK4a (26) and p21 Cip1 (27). Furthermore, MITF has been directly linked to the control of cell migration by regulating DIA1, which coordinates the actin cytoskeleton and microtubule networks at the cell periphery (28). Accordingly, MITF down-regulation by shRNA enhanced the in vivo metastatic behavior of B16 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in differentiation, MITF represses cell proliferation by activating the expression of cell-cycle inhibitors, such as p16 INK4a (26) and p21 Cip1 (27). Furthermore, MITF has been directly linked to the control of cell migration by regulating DIA1, which coordinates the actin cytoskeleton and microtubule networks at the cell periphery (28). Accordingly, MITF down-regulation by shRNA enhanced the in vivo metastatic behavior of B16 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies demonstrating changes in expression of several genes and transcription factors (e.g., cathepsin D, Pax 6, calbindin, PKC-a, and Mitf) during pluripotent stem cell differentiation 34,35 ; many of these contribute to the organization of the cytoskeleton through microfilaments, intermediate filaments, and/or microtubules [36][37][38][39][40][41][42][43] . For example, upregulation of Pax6 or PKC-a during differentiation may stabilize the cytoskeleton 44,45 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence has revealed that low levels of Mitf activity can promote proliferation (Carreira et al 2006) while high levels inhibit cell division (Carreira et al 2005;Loercher et al 2005;Wellbrock and Marais 2005). Since ␤-catenin can directly activate the Mitf-M promoter via a LEF/Tcf-binding site (Takeda et al 2000), any activation of ␤-catenin would either promote or inhibit proliferation depending on the basal level of Mitf activity in the cell.…”
Section: Discussionmentioning
confidence: 99%